Evaluation of functional plant growth-promoting activities of culturable rhizobacteria associated to tunicate maize (Zea mays var. tunicata A. St. Hil), a Mexican exotic landrace grown in traditional agroecosystems - Rivera-Hernández, Geovanny; Tijerina-Castro, Guillermo Daniel; Cortés-Pérez, Sandra; Ferrera-Cerrato, Ronald; Alarcón, Alejandro (Frontiers in Microbiology, 2024)
Tunicate maize (Zea mays var. tunicata A. St. Hil) is a landrace that constitutes a fundamental aspect of the socio-cultural identity of Ixtenco, Tlaxcala (Mexico) and represents an exotic phenotype whose kernels are enclosed in leaflike glumes. Despite multiple studies conducted worldwide on plant growth-promoting-rhizobacteria (PGPR) in commercial maize varieties grown under monoculture systems, very little is known about bacteria inhabiting native maize landraces in agroecosystems, but for tunicate maize such knowledge is non-existent. This research described and profiled functional groups of culturable rhizobacteria from tunicate maize at two phenological stages (tasseling and maturity/senescence) in a polyculture system, highlighting potential PGPR for biotechnological purposes. Ninety-five rhizobacteria were isolated and molecularly identified, and their physiological activities such as plant growth promotion, production of exogenous lytic enzymes, and antagonism against fungal pathogens were determined. The culturable rhizobacterial community associated to tunicate maize comprised forty-two genera, dominated by Bacillaceae, Comamonadaceae, Microbacteriaceae, Micrococcaceae, Oxalobacteraceae, Pseudomonadaceae, and Rhizobaceae families. At tasseling stage, the identified bacteria corresponded to Arthrobacter, Priestia, Herbaspirillum, Pseudomonas, and Rhizobium, and exhibited redundant capabilities for stimulating plant growth and nutrition, and inhibiting fungal phytopathogens. At maturity/senescence stage, the main genera Arthrobacter and Microbacterium displayed lytic capabilities to support mineralization process. We recorded potential novel rhizosphere functional bacteria such as Rhizobium, Sphingobium, and Arthrobacter which are not previously described associated to maize landraces, as well as their bioprospection as PGPR detected at plant phenological stages poorly explored (like maturity/senescence). This taxonomic and functional diversity was attributed to the application of agricultural practices as well as the rhizosphere effect during specific phenological stages. Results described the diversity and functionality of culturable rhizosphere bacteria from tunicate maize in polyculture systems that allowed us the detection of potential rhizobacteria for futher developing of biofertilizers and biocontrollers directed as biotechnology for sustainable agriculture, and for generating strategies for conservation of native plants and their microbial genetic resources.